The beneficial effect of ants on the reproductive success of Dyckia floribunda (Bromeliaceae), an extrafloral nectary plant - Vesprini, Jose Luis (2003)
Dyckia floribunda is a perennial herb from the Argentinian Chaco with extrafloral nectaries. Ants visited these nectaries while patrolling inflorescences and infructescences. We anticipated that ants attracted to extrafloral nectaries might protect the reproductive organs, increasing plant reproductive output. To evaluate the possibility of mutualism between D. floribunda and ant visitors, we determined whether ant-accessible plants showed a higher seed production than ant-excluded plants. Experimental fieldwork suggested a decrease in fruit set of ant-excluded plants compared with ant-accessible plants but the seed number per fruit was not affected by ant exclusion. Thus, total seed number per plant was highly reduced in treated spikes. Analyses of covariance confirmed these trends, indicating that total seed production per plant was strongly affected by ant exclusion. This study marks the first experimental report of this mutualistic association in Bromeliaceae.